The Role of Members of Regional People’s Representative Council (DPRD) in Making Regional Regulations (PERDA) in Eastern Seram Regency (Kabupaten Seram Bagian Timur) Maluku Province - Tuanaya, Wahab; Rengifurwarin, Zainal Abidin (Universitas Muhammadiyah Yogyakarta, 2023)
This research aims to describe the role of members of the Regional People’s Representative Council (DPRD) in making Regional Regulations (PERDA) as one of the important dimensions of regional government administration in Eastern Seram Regency (Kabupaten Seram Bagian Timur). It is also a part of the study of public administration narrowing to identifying the supports and barriers. This research used a descriptive qualitative approach. There are ten informants for this research. The instruments used to collect the required data are observations, interviews, and documentation. The findings showed that the performance of members of the SBT Regional People’s Representative Council in planning the formation is quite good, carried out through the process of drafting the RAPERDA (Regional Regulation Draft) with several academic staff and other stakeholders, discussing it in the Regional People’s Representative Council plenary meeting to hear the views of factions and commissions, then continuing to ratification and determination to become a Regional Regulations (PERDA). This role is determined by the quality of work, bad work experience, and adequate income earned by the member.